The corrosion properties of multilayer coatings deposited on stainless steel and Ti4Al6V substrates - Zykova, A.; Safonov, V.; Walkowich, J.; Rogowska, R.; Yakovin, S. (Вопросы атомной науки и техники, 2009)
Stainless steel (SS), titanium (Ti) and its alloys are the most widely used for clinical applications. The surface modification of metals with ceramic coatings by means of modern plasma methods is perspective way to reduce corrosion, to achieve better biocompatibility and to improve the performance of medical devices. The comparative analysis of the TiN, ZrO₂, Al₂O₃ and multilayer nitride/oxide coatings adhesion properties, hardness, elastic modulus, thickness, and corrosion resistance parameters at 05 N NaCl and SBF solution was made. Нержавіюча сталь та титанові сплави широко використовуються в сучасній медицині. Поверхнева модифiкацiя металів шляхом нанесення керамічних покриттів сучасними плазмовими методами э перспективним напрямком з метою зменшення корозії та покращення бiосумісності та ефективності застосування медичних приладів. Виконано порівняльний аналіз наступних властивостей плівок: адгезії, твердості, пружних модулів, корозійних властивостей різних багатошарових оксидних та нітридних покриттів. Нержавеющая сталь и титановые сплавы широко применяются в современной медицине. Поверхностная модификация металлов путем нанесения керамических покрытий современными плазменными методами является перспективным направлением для уменьшения коррозии, повышения биосовместимости и эффективности применения медицинских изделий. Проведен сравнительный анализ следующих свойств пленок: адгезии, твердости, упругих модулей, коррозионных характеристик различных многослойных нитридных и оксидных покрытий.